الاعتراض في شعر الأعشى دراسة في التجّليات النحوية والمقاصد البلاغية - حنكة, العيد (University of Eloued جامعة الوادي, 2015)
البحث هو خلاصة لتتبع ظاهرة الاعتراض النحوية وتجلياتها تغيراتها- في نموذج من الشعر الجاهلي متجسدا في مختارات من ديوان الأعشى، حيث تطرق الموضوع إلى مفاهيم نظرية حول هذه الظاهرة النحوية ثم عمد إلى استخراج نماذج مختلفة لها من الناحية التطبيقية؛ كالاعتراض في الجملة الفعلية والاسمية على جميع المستويات، مع استنباط قيمة توظيفها بلاغيا وفنيا. This paper is a summary of studying the grammatical phenomenon of subordinate clause “ITIRAD” and its aspects – changes- in a model of the pre-Islamic poetry, embodied in an anthology of EL-Aacha poems. The topic discussed some theoretical concepts about this grammatical phenomenon. Then, it turned to extract various practical models of the phenomenon such as: “ITIRAD” in the verbal and nominal sentences at all levels, in addition to detecting the value of its use rhetorically and astatically
Keywords: الاعتراض، النحو، الجملة الاسمية; ITIRAD, Grammar, nominal sentences